Instilling Character Values Through The Minangkabau Culture Subject - Putri, Elsa; Husnita, Liza; Junaidi, Juliandry Kurniawan (MSJ : Majority Science Journal, 2024)
This study is motivated by the significant moral decline observed among students, both within and outside the school environment. This issue is evident in various cases such as bullying, fighting, lack of manners, and proper conduct in daily life, including speaking, eating, and social interactions. Therefore, there is a need to emphasize the cultivation of character values through the Minangkabau Culture subject. The purpose of this study is to describe how these character values are instilled through the subject. This research uses a descriptive qualitative method, with informants consisting of the school principal and teachers of the Minangkabau Culture subject. Data were collected through observation, interviews, and documentation techniques. The findings reveal that the integration of character values in schools can be achieved through key values such as religiousness, discipline, honesty, responsibility, independence, and hard work. The cultivation of these values aims to shape better attitudes, morals, and personalities among students. In the process of character education, collaboration between parents and teachers is crucial to ensure the effectiveness of character development in schools.